Human Rights Education Potential "Preparing Students In Cultural Diversity Context" - Muhammad Khairil Mustofa (International Journal Education Multicultural of Islamic Society, 2021)
Human rights education is indispensable in preparing students who live in the context of a multicultural society. Human rights education has great potential to make a fundamental contribution in imparting the principles of democracy and human rights for students. However, the school environment where human rights education is implemented has its own problems and challenges that have the potential to hinder the implementation of human rights education. So it requires a strong commitment from schools to maximize the potential of human rights education by creating a school environment that is conducive to the implementation of democratic principles on the basis of human rights.Keywords: human rights, democracy, participation.